Social media technology usage and customer relationship performance: A capabilities-based examination of social CRM - Trainor, Kevin J.; Andzulis, James (Mick); Rapp, Adam; Agnihotri, Raj (Journal of business research, 2014)
This study examines how social media technology usage and customer-centric management systems contribute to a firm-level capability of social customer relationship management (CRM). Drawing from the literature in marketing, information systems, and strategic management, the first contribution of this study is the conceptualization and measurement of social CRM capability. The second key contribution is the examination of how social CRM capability is influenced by both customer-centric management systems and social media technologies. These two resources are found to have an interactive effect on the formation of a firm-level capability that is shown to positively relate to customer relationship performance. The study analyzes data from 308 organizations using a structural equation modeling approach.